2015
DOI: 10.1038/srep14135
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA125b-mediated Hedgehog signaling influences liver regeneration by chorionic plate-derived mesenchymal stem cells

Abstract: Although chorionic plate-derived mesenchymal stem cells (CP-MSCs) were shown to promote liver regeneration, the mechanisms underlying the effect remain unclear. Hedgehog (Hh) signaling orchestrates tissue reconstruction in damaged liver. MSCs release microRNAs mediating various cellular responses. Hence, we hypothesized that microRNAs from CP-MSCs regulated Hh signaling, which influenced liver regeneration. Livers were obtained from carbon tetrachloride (CCl4)-treated rats transplanted with human CP-MSCs (Tx) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 46 publications
2
99
0
Order By: Relevance
“…Currently, exosomes from mesenchymal stem cells (MSCs) have attracted great attention worldwide and have been proposed as one of the most efficient liver cancer therapy options [42,43]. Research discoveries have shown that exosomes from MSCs exhibit potent protective activities towards liver diseases as observed in: promoting liver regeneration [44,45], suppressing the liver inflammatory response [46], alleviating liver fibrosis [44,47], increasing the sensitivity of liver cancer cells to chemotherapeutic agents [48], and promoting the anti-tumor activities of MSCs [49]. Besides, MSC-secreting exosomes, carrying miRNAs, reduce the growth [50] and suppress angiogenesis [51] of breast cancer cells.…”
Section: Exosome-mediated Regulatory Effects In Livermentioning
confidence: 99%
“…Currently, exosomes from mesenchymal stem cells (MSCs) have attracted great attention worldwide and have been proposed as one of the most efficient liver cancer therapy options [42,43]. Research discoveries have shown that exosomes from MSCs exhibit potent protective activities towards liver diseases as observed in: promoting liver regeneration [44,45], suppressing the liver inflammatory response [46], alleviating liver fibrosis [44,47], increasing the sensitivity of liver cancer cells to chemotherapeutic agents [48], and promoting the anti-tumor activities of MSCs [49]. Besides, MSC-secreting exosomes, carrying miRNAs, reduce the growth [50] and suppress angiogenesis [51] of breast cancer cells.…”
Section: Exosome-mediated Regulatory Effects In Livermentioning
confidence: 99%
“…Similarly, hAEC have been exploited in a necroinflammatory carbon tetrachloride mouse model of liver fibrosis where intravenous hAEC administration reversed established liver fibrosis . This outcome was attributed to their polarization of macrophages from pro‐inflammatory M1 to pro‐regenerative M2 , as well as directly effects on hepatic stellate cells . In the setting of thioacetamide‐induced chronic liver failure, intrasplenically transplanted hAEC showed therapeutic efficacy while preserving HLA‐G expression .…”
Section: Preclinical Applicationsmentioning
confidence: 99%
“…Exosomes are emerging as effective therapeutic tools for different diseases because these particles can bypass biological barriers and can serve as powerful drug and gene therapy transporters, raising the exciting prospect of “cell therapy without the cells.” The administration of MSC‐derived exosomes is a potential strategy for treating liver disease . The safety and feasibility observed in early clinical trials using MSCs has resulted in increased interest in the translation of the use of these cells to the clinic .…”
Section: Msc‐derived Exosomes or Other Exosomes As A New Therapeutic mentioning
confidence: 99%